(untitled) (Academia Journal of Medicine, 2020)
Background: Macrovascular and Microvascular complications are well evaluated in DM but NAFLD is the most neglected and unevaluated complication among DM.Fibroscan is the non-invasive method for assessing liver fibrosis which has high reproducibility and accuracySubjects and Methods: It was a Case Control study. Fibrosis was assessed by fibroscan and was then quantified. Results: In our study there was a significant difference seen among the different grades of fibrosis among controls and cases (p=0.004). The mean fibrosis score too was high among cases (13.498) as compared to controls (6.052). The overall prevalence of NAFLD (F2-F4) was found to be 50% among cases as compared to 14% in controls.Conclusion: Diabetes has a significant etiological role in occurrence of NAFLD in population. Fibroscan has a substantial role in screening and diagnosing diabetics for NAFLD and fibrosis, thus advocating its use is recommended to prevent understudied and unrecognized complication of DM preventing mortality and morbidity.